2004
DOI: 10.1212/01.wnl.0000147290.68260.11
|View full text |Cite
|
Sign up to set email alerts
|

Petasites hybridus root (butterbur) is an effective preventive treatment for migraine

Abstract: Petasites extract 75 mg bid is more effective than placebo and is well tolerated as a preventive therapy for migraine. Petasites 50 mg PO bid was not significantly more effective than placebo on the primary study endpoints.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
127
0
15

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(144 citation statements)
references
References 19 publications
2
127
0
15
Order By: Relevance
“…Our meta-analysis of these two studies involving a 50-mg twice-daily dosage of butterbur 74,75 showed an odds ratio of 2.24 for a 50% reduction in frequency of migraine episodes (95% CI 0.64-7.81, p = 0.20) compared with placebo. For a 75-mg twice-daily dosage, assessed by one of these studies, 75 the odds ratio for reduction in migraine frequency was 2.16 (95% CI 1.06-4.38, p = 0.03).…”
Section: Vitamins Minerals and Herbal Agentsmentioning
confidence: 81%
“…Our meta-analysis of these two studies involving a 50-mg twice-daily dosage of butterbur 74,75 showed an odds ratio of 2.24 for a 50% reduction in frequency of migraine episodes (95% CI 0.64-7.81, p = 0.20) compared with placebo. For a 75-mg twice-daily dosage, assessed by one of these studies, 75 the odds ratio for reduction in migraine frequency was 2.16 (95% CI 1.06-4.38, p = 0.03).…”
Section: Vitamins Minerals and Herbal Agentsmentioning
confidence: 81%
“…Some natural products, such as riboflavin, butterbur, and coenzyme Q10, appear effective for migraine prophylaxis. Due to its safety, magnesium is one option for pregnant women who require migraine prophylaxis [23][24][25][26]. Nevertheless, some preventive medications have been shown to be more efficacious than others in randomized, controlled trials.…”
Section: Overview Of the Market For Migraine Preventive Treatmentmentioning
confidence: 99%
“…The drugs for migraine prophylaxis are not completely effective or safe (3). The use of complementary preventive treatments has been growing worldwide that can be decrease the frequency and severity of migraine attacks with minimal side effects (5,6).…”
Section: Introductionmentioning
confidence: 99%